Comparative analysis of U17, U20, and senior football team performances in the FIFA World Cup: from youth to senior level - Ju, W; Morgans, R; Webb, J; Cost, R; Oliva-Lozano, J. (International Journal of Sports Physiology and Performance, 2025)
Purpose: This study aimed to investigate differences in match physical and technical/tactical performance of teams across different competitive levels in international soccer: FIFA Men`s World Cup Qatar 2022 (MWC), FIFA U20 World Cup Argentina 2023 (U20WC), and FIFA U17 World Cup Indonesia 2023 (U17WC).